Electrocatalytic Oxygen Reduction Activities of Thiol-Protected Nanomolecules Ranging in Size from Au28(SR)20 to Au279(SR)84 - Sumner, Leigh; Sakthivel, Naga Arjun; Schrock, Hayley; Artyushkova, Kateryna; Dass, Amala; Chakraborty, Saumen (Journal of physical chemistry. C, 2018)
An open question in the field of nanocatalysis is how the size of nanoparticles tunes the catalysis. Here, we have investigated the kinetics of electrocatalytic oxygen reduction reactivity (ORR) of thiolate-protected gold nanomolecules (AuNMs) of sizes ranging from 1 to 2.2 nm in diameter consisting of 28, 36, 133, and 279 atoms of Au. We find that the smallest NM Au28(SR)20 [SR = 4-tert-butylbenzenethiol] demonstrates the highest overpotential of 540 mV to reach a specific current density as well as being the least selective for product formation producing ∼50:50 of HO2 – and OH–. Au36(SR)24, although being similar in size, on the contrary, is the most active NM for ORR demonstrating >3-fold lower overpotential of 160 mV and quantitatively yielding the 4e– reduced product OH–. On the basis of overpotential and product selectivity, a general reactivity trend of Au36 > Au133 > Au279 > Au28 is established, which can be qualitatively correlated to the thermochemical stability trends of the NMs. These studies suggest that even similar sized NMs can display significant differences in catalytic activity and that other contributing factors such as stability can dictate the activity outcomes, as opposed to the core size alone.